2017
DOI: 10.1002/wps.20456
|View full text |Cite
|
Sign up to set email alerts
|

Comparing three‐year extension of early intervention service to regular care following two years of early intervention service in first‐episode psychosis: a randomized single blind clinical trial

Abstract: This study aimed to determine if, following two years of early intervention service for first-episode psychosis, three-year extension of that service was superior to three years of regular care. We conducted a randomized single blind clinical trial using an urn randomization balanced for gender and substance abuse. Participants were recruited from early intervention service clinics in Montreal. Patients (N5220), 18-35 years old, were randomized to an extension of early intervention service (EEIS; N5110) or to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 37 publications
2
82
0
1
Order By: Relevance
“…This will be very demanding, mainly due to the high number of patients compared to the relatively small team of PROFIP. Some studies have shown that the major advantages of early intervention stop when it ends, suggesting that longer interventions then the initial 2 to 3 years (eg, 5 years) would be advantageous (Chang et al, , ; Malla et al, ). According to this evidence, and balancing it with the known dimensions of our team, we think that 5 years will be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…This will be very demanding, mainly due to the high number of patients compared to the relatively small team of PROFIP. Some studies have shown that the major advantages of early intervention stop when it ends, suggesting that longer interventions then the initial 2 to 3 years (eg, 5 years) would be advantageous (Chang et al, , ; Malla et al, ). According to this evidence, and balancing it with the known dimensions of our team, we think that 5 years will be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…A further challenge for effective service designs is that the benefits gained from EIS may not be maintained once the initial 2 years of intensive care is withdrawn . In response to this observation, recent controlled studies have examined whether an extension of EIS (EEIS) over 1–3 years (subsequent to the first 2 years of EIS) results in improved outcomes in symptoms and functioning compared to transfer to regular care . Our recent randomized controlled trial (RCT) showed that a 3‐year EEIS produced longer lengths of remission for positive, negative and total symptoms compared to three additional years of regular care .…”
Section: Introductionmentioning
confidence: 99%
“…In response to this observation, recent controlled studies have examined whether an extension of EIS (EEIS) over 1–3 years (subsequent to the first 2 years of EIS) results in improved outcomes in symptoms and functioning compared to transfer to regular care . Our recent randomized controlled trial (RCT) showed that a 3‐year EEIS produced longer lengths of remission for positive, negative and total symptoms compared to three additional years of regular care . On the other hand, another RCT (OPUS II) failed to show such extended benefits when using a different index for the outcome (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study assumed that since 36% of people with CHR‐P developed FEP after 3 years (Fusar‐Poli et al, ) although since then, a review found that 20% of people with CHR‐P developed FEP after 3 years (Fusar‐Poli, Rutigliano, et al, ), number of new cases of CHR‐P was at least two times higher than number of FEP although no studies exist to confirm this assumption. A further assumption made by our study is that all people with a FEP required a 3‐year EIP service provision although new service models are emerging to challenge a “one‐size‐fits‐all” approach, recognizing some individuals require shorter service support and others may benefit from longer service exposure, perhaps with a step down in intensity of service provision (Malla et al, ). Furthermore, a purely cost benefit exploration cannot take account of benefits that service users express in terms of greater satisfaction (Lester et al, ).…”
Section: Limitationsmentioning
confidence: 98%